Assessment of glycemic control protocol (STAR) through compliance analysis amongst malaysian ICU patients - Razak A.A.; Abu-Samah A.; Razak N.N.A.; Jamaludin U.; Suhaimi F.; Ralib A.; Nor M.B.M.; Pretty C.; Knopp J.L.; Chase J.G. (Dove Medical Press Ltd, 2023)
Blood; Glucose; Insulin; Intensive care units; Nutrition; Patient treatment; Sensitivity analysis; Stars; Stochastic systems; Automated modeling; Blood glucose; Blood glucose measurements; Compliance analysis; First quarter; Glycemic control; Insulin sensitivity; Malaysians; Compliance control; glucose; insulin; adult; aged; Article; automation; clinical effectiveness; clinical protocol; female; glucose blood level; glycemic control; hospital patient; human; insulin sensitivity; intensive care unit; major clinical study; Malaysian; male; nutrition; patient safety; personalized medicine; pilot study; prospective study; protocol compliance; retrospective study; stochastic model